Essays on political economy - Quinckhardt, Matthias (2022)
This dissertation contains three essays on political economy. The first essay examines the political determinants of the allocation of intergovernmental transfers in Germany with a special focus on local politics. The second essay analyses the local labor market effects of college openings in Germany and the final essay estimates the effects of a large negative shock to local populations - German casualties in World War I - on the local economy.